2016
DOI: 10.1176/appi.neuropsych.15090218
|View full text |Cite
|
Sign up to set email alerts
|

Catatonia in Neurologic and Psychiatric Patients at a Tertiary Neurological Center

Abstract: This study describes the prevalence, phenomenology, treatment, and outcome of neurological patients and psychiatric patients with catatonia at a tertiary neurological center. Clinical variables included nosological diagnoses and complications. Admission length and days with catatonia were used as outcome measures. Of 2,044 patients who were evaluated prospectively, 68 (3.32%) had catatonia, 42 (61.7%) were neurological patients, 19 (27.9%) were psychiatric patients, and 7 (10.2%) had drug-related diagnoses. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Regarding ECT, it has proven useful in the symptomatic treatment of psychosis and catatonia in ANMDARE. After careful consideration of its side‐effect profile in ANMDARE patients with status epilepticus, autonomic instability, and arrhythmias, it can be an important addition to the treatment armamentarium in ANMDARE catatonias …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding ECT, it has proven useful in the symptomatic treatment of psychosis and catatonia in ANMDARE. After careful consideration of its side‐effect profile in ANMDARE patients with status epilepticus, autonomic instability, and arrhythmias, it can be an important addition to the treatment armamentarium in ANMDARE catatonias …”
Section: Discussionmentioning
confidence: 99%
“…After careful consideration of its side-effect profile in ANMDARE patients with status epilepticus, autonomic instability, and arrhythmias, it can be an important addition to the treatment armamentarium in ANMDARE catatonias. [25][26][27] Catatonia should be regarded as one of the hallmarks of ANMDARE. Efforts are needed to increase its recognition and to identify its signs and symptoms in order to start prompt specific immunomodulatory therapy.…”
Section: Discussionmentioning
confidence: 99%
“…10 A study has reported some differentiating features that show psychiatric patients can exhibit a stuporous type of catatonia more frequently, whilst neurological patients demonstrate a mixed form of catatonia with more complications, longer hospitalisations, and more days with catatonia. 1 The index case had a similar presentation as the latter. Anti-NMDAR encephalitis may be suspected for acute presentations of catatonia where there are atypical presentations with viral-like prodrome, oddities in movements, or when the symptoms are not responding adequately to the usual treatment.…”
Section: Discussionmentioning
confidence: 80%
“…1,2 One of the common neurological conditions linked to catatonia is encephalitis, 1 and in recent years NMDAR antibody encephalitis is also being reported more frequently. 3,4 Various symptomatic presentations like psychosis, catatonia, movement disorders, short-term memory deficit and seizures have been reported in patients with synaptic autoimmunity, 4,5,6,7 which often results in patients being seen in different departments before final diagnosis.…”
mentioning
confidence: 99%
“…Estimated prevalence of catatonia among psychiatric inpatients is 7.7 % [8], whereas the prevalence in neurological settings is lower (3.3 %) [9]. However, epidemiological data on the occurrence of MC in the literature is rare.…”
Section: Conclusion Many International Guidelines Do Not Mentionmentioning
confidence: 99%